The Use Of Song In The Introduction Of English Vocabulary In Elementary School - Nawangwulan, Indah Ratih (Prosiding University Research Colloquium, 2021)
The purpose of this paper is to improve the ability of elementary school students in processing vocabulary in learning English. The media used by the teacher in this discussion is by using the media song.The learning carried out must be related to the subject matter and adapted to the age of the students. For example, Bingo, One and One, Good Morning, Happy and you know it clap your hands, One Two Three.The use of songs in learning English can be said to be the right way because in addition to motivating students in learning, fostering a cheerful atmosphere in learning, this activity is also useful in developing vocabulary, improving students' listening and pronunciation skills. Besides that, it can also improve student learning outcomes in English, and with the media, children's songs will be easy to accept the vocabulary taught. Songs can be used in learning activities for the four aspects of English, namely listening, reading, speaking, and writing.